Association of a novel circulating tumor DNA next-generating sequencing platform with circulating tumor cells (CTCs) and CTC clusters in metastatic breast cancer - Davis, Andrew A. (Breast Cancer Res, 2019)
PURPOSE: Liquid biopsies, including circulating tumor DNA (ctDNA) and circulating tumor cells (CTCs), can be used to understand disease prognosis, tumor heterogeneity, and dynamic response to treatment in metastatic breast cancer (MBC). We explored a novel, 180-gene ctDNA panel and the association of this platform with CTCs and CTC clusters. METHODS: A total of 40 samples from 22 patients with MBC were included in the study. For the primary analysis, all patients had ctDNA sequencing using the PredicinePLUS™ platform. CTCs and CTC clusters were examined using the CellSearch™ System. Clinical and pathological variables were reported using descriptive analyses. Associations between CTC count and specific genomic alterations were tested using the Mann-Whitney U test. RESULTS: Of 43 sequenced patients, 40 (93%) had at least one detectable genomic alteration with a median of 6 (range 1–22). Fifty-seven different genes were altered, and the landscape of genomic alterations was representative of MBC, including the commonly encountered alterations TP53, PTEN, PIK3CA, ATM, BRCA1, CCND1, ESR1, and MYC. In patients with predominantly hormone-receptor-positive MBC, the number of CTCs was significantly associated with alterations in ESR1 (P < 0.005), GATA3 (P < 0.05), CDH1 (P < 0.0005), and CCND1 (P < 0.05) (Mann-Whitney U test). Thirty-six percent of patients had CTC clusters, which were associated with alterations in CDH1, CCND1, and BRCA1 (all P < 0.05, Mann-Whitney U test). In an independent validation cohort, CTC enumeration confirmed significant associations with ESR1 and GATA3, while CTC clusters were significantly associated with CDH1. CONCLUSIONS: We report on a novel ctDNA platform that detected genomic alterations in the vast majority of tested patients, further indicating potential clinical utility for capturing disease heterogeneity and for disease monitoring. Detection of CTCs and CTC clusters was associated with particular genomic profiles.